Lo humano y lo animal. Consideraciones sobre los escritos recientes de W. Welsch y los últimos de L. Wittgenstein - Reguera, Isidoro (Nómadas. Critical Journal of Social and Juridical Science, 2011)
The first part of this article analizes some unpublished writtings of Prof. Wolfgang Welsch (Jena), where he tries to identify the human propium (in contrast to the animal) through the evolution-theory. The second part, following in general the considerations of the first, sketches a possible evolutionist interpretation of Wittgenstein’s philosophy, outside of her.